(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study evaluated the body mass index (BMI) and plasma lipid profile in Boerboel dogs. Body weights (BW), height (H) at shoulder and waist circumference (WC) were obtained from fifty-three Boerboels to determine the BMI while, body condition score (BCS) was determined subjectively. Also 5mls of blood was obtained from the dogs for determination of total cholesterol (TC), triglycerides (TRIG), low density lipoproteins (LDL) and high density lipoproteins (HDL). Data were presented as means ± standard deviation and results were compared using analysis of variance. Relationship between BW, H and WC was determined using regression analysis. Value was accepted significant at p < 0.05. There were no significant differences (P > 0.05) in BW, WC, BMI and GAS between male and female Boerboels, however, H was significantly (P < 0.05) higher in male (62.0 ± 1.6 cm) than female Boerboels (57.0 ± 1.5 cm). BMI and HDL were significantly (P < 0.05) lower in Boerboels <23 months (112.4 ± 2.8 Kg/m2; 36.0 ± 2.4mg/dl) compared with those 24 – 47 months (133.4 ± 1.8Kg/m2; 40.1 ± 2.2mg/dl) and >48 months (137.9 ± 1.6kg/m2; 45.8 ± 2.6mg/dl) respectively. However, there were no significant differences (P > 0.05) in TC, TRIG, HDL and LDL between Boerboels with BCS > 5 compared to those with BCS < 5. BMI linearly increased with decreasing H and WC in Boerboel dogs. It was concluded that BMI did not differ between sexes of Boerboel but differ between age categories.